Integration of Synbiotics in the management of non-motor symptoms of Parkinson’s disease - Muhammad Hamza; Areeb Muhammad Qasim; Muhammad Taha (Journal of the Pakistan Medical Association, 2025)
Madam, Parkinson's disease (PD) is a neurodegenerative disorder with motor and non-motor symptoms, including gastrointestinal issues, cognitive decline, and emotional disturbances. Recent studies highlight the potential benefits of synbiotics (probiotics and prebiotics) for alleviating these symptoms. Recent research by V Andreozzi et al indicates that synbiotic supplementation improves non-motor symptoms, such as anxiety, depression, and cognitive impairment, by modulating the gut-brain axis, as shown in improvements on MDS-UPDRS and SCOPA-AUT scales.1 Synbiotics also help manage gastrointestinal issues, such as constipation, a common problem in parkinson’s disease 2, 3. Significant results in PAC-SYM and Bristol Stool Form scores indicate improved bowel movements, suggesting synbiotics support gut health, which in turn benefits overall PD management4. Moreover, synbiotics may shift gut microbiota composition, promoting beneficial bacteria like Faecalibacterium prausnitzii, which produces butyrate—a short-chain fatty acid with neuroprotective properties. Such changes may help reduce neuroinflammation and slow PD progression. Additionally, synbiotics have been shown to reduce autonomic dysfunction, improving symptoms like dysmotility and urinary issues, which are common yet underreported in PD patients1. Though these findings are promising, the majority of research on synbiotics in PD has been conducted in Western countries. There is a pressing need to explore this therapy in Pakistan, where there is a significant prevalence of parkinson’s disease5, and limited access to effective treatments for non-motor symptoms. Understanding the role of synbiotics in local populations could offer affordable and accessible treatment options for Parkinson’s patients in South Asia. International studies have already shown the potential of synbiotics to alleviate both neurological and gastrointestinal symptoms in Parkinson’s Disease. However, further research, particularly in Pakistan, is necessary to establish optimal treatment protocols and evaluate long-term effects. Furthermore, incorporating synbiotics into the routine management of Parkinson’s patients in Pakistan could be an effective and cost-efficient strategy, particularly considering the growing body of evidence supporting their therapeutic benefits. Given the success of similar studies globally, it is essential to explore these interventions locally to enhance patient outcomes in Pakistan, significantly improve the quality of life for PD patients in the region, and contribute to the global understanding of synbiotic therapies in neurodegenerative diseases.